Evaluation of In Vitro Multiplied Accessions of Pineapple (Ananas Comosus (L.) Merr.) C V. Mauritius - Pattabi Raman S (Department of Pomology and Horticulture, College of Horticulture, 1999)
Investigations on "Evaluation ef in vitro multiplied accessions of pineapple (Ananas comosus [L.] Merr.) cv. Mauritius" were carried out in the Department of Pomology and Floriculture, College of Horticulture, Vellanikkara during 1997-1999. The major objective of the study was to evaluate the field performance of tissue culture plants of elite accessions against the tissue culture plants of unselected bulk and conventional suckers under varied fertilizer doses, to ascertain the superiority of the former over the later two and to isolate the elite accessions. During the early stage of crop growth, sucker derived plants recorded higher values for almost all the vegetative characters studied, whereas from six months after planting tissue culture plants of elite accessions were on par with sucker and showed significant superiority over the unselected bulk. Total dry matter production as well as dry matter partitioning were higher for tissue culture plants of elite accessions than tissue culture plants of unselected bulk. The former also showed early flowering with longer flowering phase than the later. The fruit and yield parameters also showed superiority of tissue culture plants of elite accessions over that of unselected bulk and the values were on par with suckers. Among the elite accessions, TK 3 (Ti) and KT 5 (T2) performed well and recorded the maximum estimated yield (77.0 tonnes), whereas tissue culture plants of unselected bulk recorded an estimated yield of 49 tonnes only. There was not much variation among the treatments in all the quality parameters studied, except for TSS:Acid ratio All the tissue culture plants including unselected bulk produced more number of suckers and slips than sucker derived plants.